Development of a respiratory syncytial virus vaccine using human hepatitis B core-based virus-like particles to induce mucosal immunity. Issue 24 (2nd June 2021) - Huang, Jen-Min; Wang, Shih-Yun; Lai, Mei-Ru; Tseng, Yu-Kai; Chi, Ya-Hui; Huang, Li-Min
Abstract: Background: Respiratory syncytial virus (RSV) is an important viral pathogen responsible for severe infection of the lower respiratory tract in children under the age of 5 years. No vaccines against RSV are currently in clinical use. Vaccine-associated enhanced respiratory disease (ERD) caused by excess Th2 type responses was observed in a clinical trial of formalin-inactivated RSV (FI-RSV) in antigen-naïve infants. Thus, inducing a balanced immune response is a crucial issue in the development of an RSV vaccine. Methods: In this study, we constructed, expressed, and purified a recombinant RSV vaccine candidate (i.e., HRØ24) containing the two heptad repeat regions and the antigenic sites Ø, II, and IV of the RSV F protein. The RSV vaccine candidate was intranasally administrated to BALB/c and C57BL/6 mice in combination with virus-like particles (VLPs) derived from the core protein of the hepatitis B virus (HBc). Mucosal immunity to HRØ24 was then assessed. Results: Intranasal administration of HBc VLPs in combination with HRØ24 induced serum IgGs against HRØ24 as well as lung HRØ24-specific sIgAs in both C57BL/6 and BALB/c mouse models. The secretion of IFN-γ from splenocyte re-stimulation and an elevated ratio of serum IgG2a to IgG1 indicated that the immune response induced by the HBc VLPs/HRØ24 mixture was Th1-biased. Weight loss of <5% and no to low eosinophil infiltration was observed in histological analysis of the lung following a challenge with the RSV A2 strain. These results suggest that the HBc VLPs/HRØ24 combination conferred substantial partial protection against RSV-induced illness in mice. Conclusions: Long-term immunity to RSV-induced illness was achieved via intranasal vaccination using a mixture of HBc VLPs and HRØ24 in mouse models.